Engineering of itraconazole nano- and microparticles with improved pharmaceutical performance - Mugheirbi, Naila A. (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2016)
Itraconazole (ITR) is an antifungal drug with limited bioavailability due to its poor aqueous solubility. In this work, ITR was used to investigate unexplored and/or previously reported as infeasible formulation approaches such as, the impact of nanonization at elevated temperatures, crystal habit tuning and solid state manipulation, including unexplored state of matter such as liquid crystals, on drug’s pharmaceutical properties. A bottom up approach to the production of amorphous ITR nanoparticles (NPs), composed of 100% drug, with a particle diameter below 250 nm, using heat induced evaporative antisolvent nanoprecipitation (HIEAN) from acetone was developed. The NPs demonstrated improved apparent solubility and dissolution in simulated gastro-intestinal conditions when compared to spray dried ITR microparticles. NPs produced with polyethylene glycol (PEG) or its methoxylated derivative (MPEG) as a stabilizer possessed smaller particle size with narrower particle size distribution and enhanced apparent solubility. MPEG stabilized NPs gave the greatest ITR supersaturation levels (up to 11.6 ± 0.5 pg/ml) in simulated gastric fluids. Dynamic vapor sorption data indicated no solid state changes in NP samples with water vapor at 25 °C, while crystallization was apparent at 50 °C.
Keywords: Pharmacy & Phamaceutical Sciences, Ph.D.; PhD Trinity College Dublin, 2016